Effect of molecular weight on the interfacial and emulsifying characteristics of rice glutelin hydrolysates. (July 2022) - Yang, Zhenyu; Dai, Lei; Sun, Qingjie; McClements, David Julian; Xu, Xingfeng
Abstract: Previously, it has been shown that rice glutelin with a degree of hydrolysis of 2% (DH2) can form stable oil-in-water emulsions, but the stabilization mechanism has not yet been elucidated. In this study, the molecular, interfacial, and emulsifying properties of DH2 were investigated to better understand the structure-function relationships of this emulsifier. Peptides with relatively small (<5 kDa), medium (5–10 kDa), and large (>10 kDa) molecular weights were separated from DH2 by ultrafiltration. The large and medium peptides exhibited the highest surface hydrophobicity and intrinsic fluorescence intensity, respectively. Dynamic interfacial tension and quartz crystal microbalance with dissipation (QCM-D) analysis was utilized to characterize the interfacial properties. The large peptides exhibited a faster adsorption rate and a greater reduction in interfacial tension than the others. QCM-D indicated that the properties of the interfacial layers formed by the peptides were different during adsorption or desorption for all samples. The properties of the emulsions formed using the different peptides were characterized by confocal laser scanning microscopy, particle size, flocculation index, and coalescence index analysis. The storage stability of the emulsions increased as the molecular weight of the peptides used to coat the oil droplets increased, which may have been due to an increase in the steric repulsion caused by thicker interfacial layers. These results indicate that the large peptides in DH2 play the most important role in forming and stabilizing emulsions. This knowledge may be used to increase the utilization of hydrolyzed rice proteins as plant-based emulsifiers in foods and beverages. Graphical abstract: Image 1 Highlights: Small, medium, and large peptides were separated from rice glutelin hydrolysates. The "molecule-interfacial-emulsion" multiscale methodology was employed. Molecular weight had an important role in structure properties. The conformation was changed for all samples at the oil-water interface. Emulsion stability of hydrolysate was mainly contributed by large peptides.